How Learning Motivation Influences Feedback Experience and Preference in Chinese University EFL Students - Gan, Zhengdong (Frontiers in Psychology, 2020)
Drawing on the argument that students’ different learning behaviors, including their perceptions of and engagement with feedback, could have roots in learners’ fundamental motivational characteristics, this study examines how different second language learning motivational variables may predict university EFL (English as a foreign language) students’ feedback experience and preference. Data were collected from EFL students from three universities in an Asian region (N = 409) through three self-report questionnaires. Results of structural equation modeling (SEM) revealed that different components of the second language learning motivational construct appear to display differential associations with EFL students’ feedback experience and preference. In particular, this study brought to light the crucial role of attitudes to classroom English learning and intended learning effort as essential mediating motivational variables in predicting how EFL students conceive of and act on feedback. The findings of this study also provide significant insights into a complex and dynamic view of how student preference for different types of feedback actually works in the feedback process. The authors conclude by arguing that EFL teachers need to shoulder the burden of making the EFL classroom a supportive environment that promotes a positive self-concept and self-confidence as the first step toward stimulating students’ active feedback use, and that conditions need to be created to allow for connection of students’ preference for learning process-oriented feedback to action to maximize the pivotal role that students play in the classroom and learning process.